Acceptability and quality evaluation of vitamin C fortified baked brownies using ampalaya (Momordica charantia Linn.,) powder. - Lequigan, Raymond
In the Philippines, vitamin C deficiency and hunger have been prevalent issues that are essentially anchored to the availability and quality of food products. This study focused on utilizing the vitamin C available in ampalaya powder (AP) in the fortification of baked brownies. The Ap produced using a food dehydrator had a light-green color with slight hints of brown and dark-green particles, 0.45g/cm3 bulk density, 14.43% moisture content on dry basis, 0.54 water activity, 7.17 Water Absorption Index (WAI), and 17.54mg/100g vitamin C. the brownies were prepared by incorporating 15%, 30%, 45%, and 60% AP to substitute all-purpose flour in the original formulation. Results shows that 15% partial substitution was considered the Most Preferred Formulation (MPF). It was also revealed that formulations with higher AP proportions had lower acceptability ratings in terms of flavor, sweetness, mouthfeel, and general acceptability. The control and MPF formulation were further tested for consumer preference, nutritional composition, texture quality, and costing. In terms of nutritional composition, MPF had a notable increase in ash and vitamin C contents. Simultaneously, a notable decrease in crude fat and energy contents was also observed. Moreover, Texture Profile Analysis (TPA) revealed that incorporation of AP increased the cohesiveness and chewiness of the MPF. Additionally, consumer preference test determined that the MPF was well-liked with a 49% preference rating. Meanwhile, costing revealed that the MPF was more expensive. Overall AP enhanced the nutritional composition and vitamin C content of baked brownies. Recommendations include conducting field study and investigate its stability.